An Analysis of Malay Folklore Characters: Preserving Tradition with Scented Candles: Preserving Tradition with Scented Candles - Abdul Rafaie, Nurul Atiqah; Kamaruddin, Norfadilah (Research in Management of Technology and Business, 2024)
Folktales are an important part of culture and tradition, serving as a symbol of the identity of a community. This study aims to explore how Malay folklore characters can be creatively portrayed using scented candles or candles with hidden messages inside. The candles were designed with carefully selected scents to evoke the individuality and essence of each character, creating a multi-sensory experience that promotes cultural heritage and ignites the curiosity of Malaysians. The research project employed qualitative methods, including visual analysis and interviews. The goal of this study is to raise awareness of Malaysia’s cultural heritage, encourage people to participate in a unique concealed scented candle experience and honor the rich traditions of Malay folklore. This product is intended for tourists, folklore enthusiasts, and gift shoppers.